Peran Guru BK dalam Menerapkan Layanan di Sekolah SMPN 2 Telukjambe Timur - Haura Taqiya Kamila; Dinda Riswana; Azzahra Kurnia Nur Ramadhan; Deni Ramdani (Lembaga Pengembangan Kinerja Dosen, 2025)
Guidance and counseling is assistance provided to students, either individually or in groups, so they can become more independent and develop optimally in various areas such as personal relationships, social relationships, learning, and careers. This assistance is provided through several types of services and activities in accordance with applicable regulations. Observation and interviews are among the methods used by guidance and counseling teachers to gather information in carrying out their duties at school. Guidance and counseling services at SMPN 2 Telukjambe Timur run smoothly. Guidance and counseling teachers play a creative, innovative, interactive, and communicative role in carrying out their duties. In addition, guidance and counseling teachers are also supported by the presence of Islamic Religious Education (PAI) teachers. The partnership between guidance and counseling teachers is very good and very important, because both have the same goal: to shape good character in students at school.